Jihadism expansion in Egypt after 2011 on the example of Ansar Bayt al-Maqdis, Sinai Province and other structures (Economic and Political Thought, 2016)
Since the ‘January 25 Revolution’ the Egyptian territory has becomea subject of increased interest of various jihadist structures. The Sinai Peninsulaplays a special role in their development as it is an area of strategicimportance because of its proximity to Israel and Cairo, one of the centers ofthe Arab world. Among such structures there is Sinai Province, which is a relativelynew player on the scene of the Egyptian political violence, althoughnow this entity has the greatest influence on this territory. The group derivesfrom Ansar Bayt al-Maqdis, a group that appeared in the northern part of theSinai Peninsula in 2011. In 2013 it transformed into a branch of the IslamicState. Despite significant operational capabilities, Sinai Province is not theonly jihadi structure functioning in Egypt. New armed groups opposed tostate structures are formed, which include Ajnad Misr or the Allied PopularResistance Movement. The article aims to present the process of jihadismexpansion in Egypt after 2011, tying it with destabilisation of the state’sinternal structures, reflected by frequent changes of authorities.